Rekonstruksi Epistemologi Spiritual Islam di Era Artificial Intelligence: Integrasi Teologi, Filsafat, dan Tasawuf sebagai Paradigma Pengetahuan Baru - Ali Hasan Siswanto; Aslam Saad (Jurnal Teologi Islam, 2026)
The rapid advancement of Artificial Intelligence (AI) has fundamentally transformed the landscape of knowledge production, dissemination, and validation, including within the field of Islamic Studies. This transformation has given rise to a crisis of spiritual epistemology, characterized by the increasing fragmentation of the relationship among theology (kalām), Islamic philosophy (falsafah), and Sufism (taṣawwuf) as the three principal pillars of the Islamic intellectual tradition. At the same time, the dominance of the positivist paradigm in contemporary academic scholarship has increasingly marginalized revelation, intuition, and spiritual experience as legitimate sources of knowledge. Although research on AI in Islamic Studies has expanded significantly, it has predominantly focused on issues of ethics, Islamic law, education, and the digitalization of religious services. Existing studies have yet to adequately examine the implications of AI for the reconstruction of Islamic epistemology, nor have they proposed a conceptual model that integrates revelation, reason, spiritual experience, and artificial intelligence within a unified epistemic framework. Addressing this gap, this article adopts an integrative Islamic epistemological approach by synthesizing perspectives from theology, Islamic philosophy, Sufism, and the philosophy of technology. This study employs a qualitative conceptual library research design through a critical literature review, philosophical analysis, and conceptual synthesis of both classical and contemporary scholarship. The article argues that AI should be understood as an epistemic instrument that extends human cognitive capacities rather than as an epistemic authority capable of replacing revelation, reason, and spiritual experience. As its principal theoretical contribution, this study proposes the Integrated Spiritual Epistemology Framework (ISEF) as a new epistemological paradigm that reconstructs the relationship among revelation, reason, maʿrifah (spiritual knowledge), and artificial intelligence within the framework of contemporary Islamic knowledge. This framework is expected to enrich the theory of Islamic epistemology, strengthen the dialogue between Islamic Studies and the philosophy of technology, and open new avenues of research on the authority of religious knowledge in the age of artificial intelligence.